2014
DOI: 10.3390/ijerph110100866
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Neighborhood Influences on Small-Area Variations in Intimate Partner Violence Risk: A Bayesian Random-Effects Modeling Approach

Abstract: This paper uses spatial data of cases of intimate partner violence against women (IPVAW) to examine neighborhood-level influences on small-area variations in IPVAW risk in a police district of the city of Valencia (Spain). To analyze area variations in IPVAW risk and its association with neighborhood-level explanatory variables we use a Bayesian spatial random-effects modeling approach, as well as disease mapping methods to represent risk probabilities in each area. Analyses show that IPVAW cases are more like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 78 publications
(134 reference statements)
3
55
0
6
Order By: Relevance
“…exp(−0.3302) − 1 = −0.2812 (15) exp(−0.5331) − 1 = −0.4132 (16) Using the same calculation method, we estimated that the relative risk of burglary and non-motor vehicle theft will increase by 67.30% and 46.96%, with an increase of one standard deviation in bar density, respectively (Equations (17) and (18)). Table 4 shows the posterior means of the covariance/correlation matrix of the random effects.…”
Section: Analysis Of Risk Factorsmentioning
confidence: 93%
See 2 more Smart Citations
“…exp(−0.3302) − 1 = −0.2812 (15) exp(−0.5331) − 1 = −0.4132 (16) Using the same calculation method, we estimated that the relative risk of burglary and non-motor vehicle theft will increase by 67.30% and 46.96%, with an increase of one standard deviation in bar density, respectively (Equations (17) and (18)). Table 4 shows the posterior means of the covariance/correlation matrix of the random effects.…”
Section: Analysis Of Risk Factorsmentioning
confidence: 93%
“…Policing rooms are set up by local police stations and staffed by several police officers to guarantee neighborhood's security. The relationship between policing and crime has been investigated in previous studies [15,27].…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Research has found that concentrated disadvantage is the factor most strongly associated with crime, even after controlling for individual characteristics [1,8]. Immigration has also been related to crime rates, and previous research has shown that higher levels of ethnic heterogeneity are related to higher levels of crime [1,9,10]. Residential instability is also a relevant factor in social disorganization theory.…”
Section: Introductionmentioning
confidence: 99%
“…Most research has focused on residential burglary [13][14][15], juvenile delinquency [16,17], homicides [1,18,19], and robbery and assaults [18,19]. Interest is also growing in studying this relationship in other crimes that tends to occur 'behind closed doors' [20] such as intimate partner violence [9,10] or child maltreatment [21].…”
Section: Introductionmentioning
confidence: 99%